Intermatrix synthesis: easy technique permitting preparation of polymer-stabilized nanoparticles with desired composition and structure - Ruiz, Patricia (Springer, 2011)
The synthesis of polymer-stabilized nanoparticles (PSNPs) can be successfully carried out using intermatrix synthesis (IMS) technique, which consists in sequential loading of the functional groups of a polymer with the desired metal ions followed by nanoparticles (NPs) formation stage. After each metal-loading-NPs-formation cycle, the functional groups of the polymer appear to be regenerated. This allows for repeating the cycles to increase the NPs content or to obtain NPs with different structures and compositions (e.g. core-shell or core-sandwich). This article reports the results on the further development of the IMS technique. The formation of NPs has been shown to proceed by not only the metal reduction reaction (e.g. Cu(0)-NPs) but also by the precipitation reaction resulting in the IMS of PSNPs of metal salts (e.g. CuS-NPs).